Biofilm Inhibition of Citrus Fruits against Nosocomial Pathogens: A Systematic Review - Bassig, Elijah Carl C.; Clemente, Nicole Ann A.; Espiritu, Eunice B.; Ilagan, Christine Megan A.; Martinez, Crissylette Joy C.; Pineda, Marielle Laiza H.; Raguindin, Pamela Julles P.; Santos, Dazy Gale V.; Bremner, Pamela Rose F. (Asian Journal of Biological and Life Sciences)
Aim/Background: A mechanism common to nosocomial pathogens to survive on varying environments is the ability to form biofilms. Biofilms adhere to biotic or abiotic surfaces and house mono or poly cell communities and allow them to survive hostile environments. This systematic review intends to discuss biofilm inhibitory effects of various citrus fruits against nosocomial pathogens and its phytochemical contents. Materials and Methods: Studies focusing on biofilm inhibition in nosocomial pathogens, those that were able to inhibit the biofilm, citrus fruit available in the Philippines, studies that utilized solvent for obtaining the citrus extract, and those that were written in English were sought. All available findings obtained from the filtered studies under the said criteria were further analyzed, and then sorted out. Results: Of the seven studies, with one study utilizing two extracts; two extracts were able to completely inhibit biofilm growth at 100%; while one was able to inhibit at 90%; another was able to inhibit at 81%; followed by 68% inhibition; then two extracts were able to inhibit biofilm at 53.85%; lastly was at 50%. Conclusion: Rutin was shown to be able to downregulate luxS gene and wabG gene which are responsible for quorum-sensing and capsular polysaccharide respectively. Naringin exhibited reduce exopolysaccharide (EPS) and biofilm biomass. Lastly of the flavonoids, naringenin downregulates tfB, gtfC, comD, comE, and luxS expression which are essential in the formation of biofilm. Limonin, a type of limonoid, was suggested to target and disrupt cell-to-cell signaling of a biofilm. Limonene, a monoterpene, acts by reducing the attachment of a biofilm to surfaces.
Keywords: Biofilm; Biofilm inhibition; Citrus; Nosocomial pathogens; Phytochemicals